Analysis Of The Internal Control System Of Pettty Cash Fund Demand At PT Bank Syariah Indonesia KCP Surabaya Ampel Mas Mansyur - Cholifatul Rochmah; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2024)
Cash is an asset that has an important component in company operations. Petty cash has a high level of vulnerability to theft and misuse. Controlling petty cash management is one of the things that can help a company achieve success. An internal control system for cash that is carried out optimally can have a positive impact on the continuity of company operations. On the other hand, if the implementation of internal control over petty cash is less than optimal, it can increase the possibility of fraud and asset theft. In this research, researchers used descriptive qualitative methods. Having a good internal control system in a company can help the company to manage company finances efficiently regarding petty cash expenditures. The results of the research reveal that the internal control of petty cash at PT Bank Syariah Indonesia has been running well and in accordance with the procedures set by the board of directors